ChemInform Abstract: A Simple Route to Polysubstituted Indoles Exploiting Azide Induced Furan Ring Opening. Issue 7 (29th January 2015) - Abaev, Vladimir T.; Plieva, Anastasiya T.; Chalikidi, Petrakis N.; Uchuskin, Maxim G.; Trushkov, Igor V.; Butin, Alexander V.
Abstract An efficient indole synthesis based on thermolysis of 2‐(2‐azidobenzyl)furans (III) and (VI) with attack of the formed nitrene moiety onto the ipso position of furan ring is developed.